2019
DOI: 10.1177/1066896919839781
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Adenocarcinomatous and Neuroendocrine Tumor of the Urinary Bladder With Concomitant Carcinoma In Situ: A Case Report With a Comprehensive Immunohistochemical Analysis and Review of the Literature

Abstract: Mixed adenoneuroendocrine carcinomas are rare and usually occur in the gastrointestinal tract. Although there have been several investigations regarding their developmental mechanism, the molecular origin of these tumors remains unclear. In this article, we present an exceedingly rare case of a mixed tumor of the urinary bladder with an adenocarcinomatous and a neuroendocrine component and a concomitant urothelial carcinoma in situ (CIS). Due to this extraordinary combination of tumor components, our goal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Over half of the primary urinary NECs are mixed with other histological components (5,6), and more than 90% of these reports of non-neuroendocrine components were of urothelial carcinoma, followed by squamous cell carcinoma, lymphoma, sarcoma, and adenocarcinoma, in order of frequency. We summarized published cases of mixed neuroendocrine and adenocarcinomatous tumor of the urinary system between 1990 and 2023 (Table 1) (7)(8)(9)(10)(11)(12)(13). The male-tofemale ratio was 7:1, with a median of 61 years, and it can occur in the bladder, ureter and urethra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of the primary urinary NECs are mixed with other histological components (5,6), and more than 90% of these reports of non-neuroendocrine components were of urothelial carcinoma, followed by squamous cell carcinoma, lymphoma, sarcoma, and adenocarcinoma, in order of frequency. We summarized published cases of mixed neuroendocrine and adenocarcinomatous tumor of the urinary system between 1990 and 2023 (Table 1) (7)(8)(9)(10)(11)(12)(13). The male-tofemale ratio was 7:1, with a median of 61 years, and it can occur in the bladder, ureter and urethra.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many scholars support the theory of MiNEN is hypothesized to originate from monoclonal pluripotent stem cells that differentiate bidirectionally when stimulated with certain factors, which could explain the mixed histological features in urogenital NECs (19). Tränkenschuh et al (11) reported the case of a patient with primary adenoneuroendocrine carcinoma of the bladder combined with in situ urothelial carcinoma and observed significant similarities in the molecular features between these carcinomas, thereby highlighting their common clonal origin. Another postulated theory is that ureteral MiNEN may be caused by conversion of non-neuroendocrine to neuroendocrine components during tumor progression, including originating from residual urachus epithelium, or cystitis glandularis and intestinal anisocytosis, which would seem to explain the mix of adenocarcinoma components in MiNEN.…”
Section: Discussionmentioning
confidence: 99%